Institutionalizing Corporate Social Responsibility Within Corporate Communications In The Survey Of The Malaysian Organizations - Zulhamri, Abdullah; Yuhanis, Abdul Aziz; Tai, Lit Cheng (2010)
Purpose - The purpose of this paper is to develop empirical measures of Asian corporate social responsibility (CSR) based on a David’s dual process model of CSR for Malaysian government linked corporations (GLC) and public listed companies (PLC). Design/methodology/approach - A survey consisting of 285 respondents was conducted and a structural equation model was used to test the relationship between the constructs. An instrument to measure CSR practices mainly focusing on CSR relational, CSR ethical/moral, and CSR discretionary is developed to see greater impacts on corporate reputation, legitimacy and corporate culture. Findings - The findings show CSR antecedents have significantly formed through the formalization of corporate communication management in the Malaysian organizations. The structural model provides evidence that CSR initiatives have a significant direct impact on corporate reputation. It was also found that CSR initiatives are positively related to culture and legitimacy. The culture had a significant positive effect on corporate reputation. Culture construct was also found to mediate partially the relationship between CSR initiatives and corporate reputation. On the other hand, it was found that legitimacy is partially mediated CSR initiatives but not related to corporate reputation. Practical implications - The study acknowledges the increase in CSR initiatives within existing corporate communication practices in GLCs & PLCs in their quest to gain public legitimacy and corporate governance. Originality/value - The study contributes to the CSR literature by explicitly linking CSR to corporate reputation and corporate culture and by developing proposed model of CSR that can be used in exploring a critical dimension in management of corporate identity in an Asian country.